Booster immunization of meningococcal meningitis vaccine among children in Hangzhou, China, 2014-2019 - Che, Xinren; Liu, Yan; Wang, Jun; Xu, Yuyang; Zhang, Xuechao; Gu, Wenwen; Jiang, Wei; Du, Jian; Zhang, Xiaoping (PloS one, 2021)
Despite China's Expanded Program on Immunization (EPI) provides 2 doses of group A and group C meningococcal polysaccharide vaccine (MPV-AC) for children at 3 years and 6 years old, more self-paying group ACYW135 meningococcal polysaccharide vaccines (MPV-ACYW135) have been used as an alternative to MPV-AC to prevent Neisseria meningitidis serogroup C,Y,W135. We provide recommendations for Chinese booster immunization of meningococcal meningitis vaccine by analyzing the service status of MPV-AC and MPV-ACYW135. Reported data of routine immunization coverage from all districts of Hangzhou registered in the China Information Management System For Immunization Programming (CIMSFIP) between 2014 to 2019 were described and evaluated. Descriptive epidemiological methods were used to characterize the data. Adverse event following immunization (AEFI) were collected from Chinese national adverse event following immunization information system (CNAEFIIS) to compare the safety of MPV-AC and MPV-ACYW135. 1376919 doses of booster immunization of meningococcal meningitis vaccine (MenV) in CIMSFIP were conducted in China Hangzhou from 2014 to 2019, with reported immunization coverage rates above 95%. The proportion of children using MPV-ACYW135 increased from 12.63% in 2014 to 29.45% in 2019. The incidence of AEFI of MPV-AC and MPV-ACYW135 were 49.75 per 100,000 and 45.44 per 100,000, respectively, without statistical difference. Children in Hangzhou had high booster immunization of MenV coverage. The use amount and use rate of MPV-ACYW135 increased year by year, indicating more and more parents had chosen MPV-ACYW135 as an alternative to MPV-AC at their own expense for children. The use proportions of MPV-ACYW135 were different in urban, suburban and rural areas. Both MPV-AC and MPV-ACYW135 were safe for children.